An Altered Metabolism in Leukocytes Showing in vitro igG Memory From SARS-CoV-2-Infected Patients - Fanelli, G.; Gevi, F.; Zarletti, G.; Tiberi, M.; De Molfetta, V.; Scapigliati, G.; Timperio, A. M. (Frontiers in Molecular Biosciences, 2022)
Coronavirus disease 2019 (COVID 19) is a systemic infection that exerts a significant impact on cell metabolism. In this study we performed metabolomic profiling of 41 in vitro cultures of peripheral blood mononuclear cells (PBMC), 17 of which displayed IgG memory for spike-S1 antigen 60–90 days after infection. By using mass spectrometry analysis, a significant up-regulation of S-adenosyl-Homocysteine, Sarcosine and Arginine was found in leukocytes showing IgG memory. These metabolites are known to be involved in physiological recovery from viral infections and immune activities, and our findings might represent a novel and easy measure that could be of help in understanding SARS-Cov-2 effects on leukocytes.